Construction technology erecting substructures and superstructures - Laleman, Joseph P.; Meridian education Corporation (Lawrencville, NJ : Cambridge Educational, 2004)
Outlines the basic elements of designing and erecting substructures and superstructures
Executive producer, Twila Sears
DVD format
Keywords: Building; Structural engineering; Construction industry